Molecular Mechanism of Hippo–YAP1/TAZ Pathway in Heart Development, Disease, and Regeneration - Chen, Xiaoqing; Li, Yilang; Luo, Jiandong; Hou, Ning (Frontiers in Physiology, 2020)
The Hippo–YAP1/TAZ pathway is a highly conserved central mechanism that controls organ size through the regulation of cell proliferation and other physical attributes of cells. The transcriptional factors Yes-associated protein 1 (YAP1) and PDZ-binding motif (TAZ) act as downstream effectors of the Hippo pathway, and their subcellular location and transcriptional activities are affected by multiple post-translational modifications (PTMs). Studies have conclusively demonstrated a pivotal role of the Hippo–YAP1/TAZ pathway in cardiac development, disease, and regeneration. Targeted therapeutics for the YAP1/TAZ could be an effective treatment option for cardiac regeneration and disease. This review article provides an overview of the Hippo–YAP1/TAZ pathway and the increasing impact of PTMs in fine-tuning YAP1/TAZ activation; in addition, we discuss the potential contributions of the Hippo–YAP1/TAZ pathway in cardiac development, disease, and regeneration.